Antibiotic self-medication and antibiotic resistance: Multilevel regression analysis of repeat cross-sectional survey data in Europe - Alistair Anderson (REGION, 2021)
Antibiotic resistance is a global public health issue with several anthropogenic drivers, including antibiotic consumption. Recent studies have highlighted that the relationship between antibiotic consumption and antibiotic resistance is contextualised by a variety of socioeconomic, cultural, and governance-related drivers of consumption behaviour and contagion that have been underexamined. A potential complication for research and policy is that measures of antibiotic consumption are often reliant on prescribing or sales data which may not easily take into account the dynamics of community consumption that include self-medication; for example, the preservation and use of leftover medication or the obtaining of antibiotics without a prescription. This study uses repeated cross-sectional survey data to fulfil two core aims: firstly, to examine the individual-level and national-contextual determinants of self-medication among antibiotic consumers in European countries, and secondly, to examine the relationship between self-medication behaviour and antibiotic resistance at the national level. This study is particularly novel in its application of a multilevel modelling specification that includes individual-level factors with both time-variant and persistent national characteristics to examine antibiotic consumption behaviours. The key findings of the study are that survey respondents in countries with persistently higher levels of inequality, burdens of out-of-pocket health expenditure, and corruption have an increased probability of self-medicating with antibiotics. The study also highlights that overall levels of antibiotic consumption and antibiotic self-medication do not correlate and are associated heterogeneously with changes in different pathogen/antibiotic pairs. In summary, the study emphasises that antibiotic stewardship and antibiotic resistance, whilst related by biological mechanisms, are also inherently social issues. Attempts to improve antibiotic stewardship and address the challenge of antibiotic resistance should also attend to structural challenges that underlie challenges to antibiotic stewardship in the community, such as the effects of inequality and reduced access to healthcare services.
Keywords: 330